Kinetic Analysis of the Reduction Processes of a Cisplatin Pt(IV) Prodrug by Mesna, Thioglycolic Acid, and Thiolactic Acid - Yanqing Xia; Hongwu Tian; Yanlei Li; Xinru Yang; Jinming Liu; Chunli Liu; Li Zhou; Lincai Zhang; Tiejian Li; Tiesheng Shi (Journal of Chemistry)
Although Mesna is an FDA-approved chemotherapeutic adjuvant and an antioxidant based largely on its antioxidative properties, kinetic and mechanistic studies of its redox reactions are limited. A kinetic analysis of the reduction processes of cis-diamminetetrachloroplatinum(IV) (cis-[Pt(NH3)2Cl4], a cisplatin Pt(IV) prodrug) by thiol-containing compounds Mesna, thioglycolic acid (TGA), and DL-thiolactic acid (TLA) was carried out in this work at 25.0°C and 1.0 M ionic strength. The reduction processes were followed under pseudo-first-order conditions and were found to strictly obey overall second-order kinetics; the observed second-order rate constant k′ versus pH profiles were established in a wide pH range. A general reaction stoichiometry of Δ[Pt(IV)] : Δ[Thiol]tot = 1 : 2 was revealed for all the thiols; the thiols were oxidized to their corresponding disulfides which were identified by mass spectrometry. Reaction mechanisms are proposed which involves all the prololytic species of the thiols attacking the Pt(IV) prodrug in parallel, designating as the rate-determining steps. Transient species chlorothiol and/or chlorothiolate are formed in these steps; for each particular thiol, these transient species can be trapped rapidly by another thiol molecule which is in excess in the reaction mixture, giving rise to a disulfide as the oxidation product. The rate constants of the rate-determining steps were elucidated, revealing reactivity enhancements of (1.4–8.9) × 105 times when the thiols become thiolates. The species versus pH and reactivity of species versus pH distribution diagrams were constructed, demonstrating that the species ‒SCH2CH2SO3‒ of Mesna largely governs the total reactivity when pH > 5; in contrast, the form of Mesna per se (mainly as HSCH2CH2SO3‒) makes a negligible contribution. In addition, a well-determined dissociation constant for the Mesna thiol group (pKa2 = 8.85 ± 0.05 at 25.0°C and μ = 1.0 M) is offered in this work, which was determined by both kinetic approach and spectrophotometic titration method.